Holocene and Pleistocene pluvial periods in Yemen, southern Arabia - Fleitmann, Dominik; Burns, Stephen J.; Pekala, Marek; Mangini, Augusto; Al-Subbary, Abdulkarim; Al-Aowah, Mohammad; Kramers, Jan; Matter, Albert (Quaternary science reviews, 2011)
Arabia is an important potential pathway for the dispersal of Homo sapiens (“out of Africa”). Yet, because of its arid to hyper-arid climate humans could only migrate across southern Arabia during pluvial periods when environmental conditions were favorable. However, knowledge on the timing of Arabian pluvial periods prior to the Holocene is mainly based on a single and possibly incomplete speleothem record from Hoti Cave in Northern Oman. Additional terrestrial records from the Arabian Peninsula are needed to confirm the Hoti Cave record. Here we present a new speleothem record from Mukalla Cave in southern Yemen. The Mukalla Cave and Hoti Cave records clearly reveal that speleothems growth occurred solely during peak interglacial periods, corresponding to Marine Isotope Stages (MIS) 1 (early to mid-Holocene), 5.1, 5.3, 5.5 (Eemian), 7.1, 7.5 and 9. Of these humid periods, highest precipitation occurred during MIS 5.5 and lowest during early to middle Holocene.